2008
DOI: 10.1196/annals.1417.009
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates for Sexual Preference and Motivation in the Female and Male Rat

Abstract: Rodents identify a mating partner by using olfactory cues. Female rats in estrus spend a longer time sniffing odors of sexually active males when physical contacts are hampered. Sexually active males are attracted by odors of receptive females. The preference in either sex disappears when the subjects are gonadectomized, an effect reversible by supplement with estrogen or testosterone. Thus, circulating sex steroids determine the odor preference in both sexes. In both sexes, olfactory cues get to the basal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 58 publications
(119 reference statements)
3
33
1
3
Order By: Relevance
“…While it has been documented that some of these brain regions (e.g. POA) can vary in neuronal properties with social structure, hormone levels, and copulation in males [White and Fernald, 1993;Prince et al, 1998;White et al, 2002;Sakuma, 2008], an analogous situation in females is unlikely in the current study. Female X. nigrensis breed year-round ; we did not detect any relationship between circulating estradiol levels and neuroligin-3 expression and females were not allowed to physically interact with males (online suppl.…”
Section: Neuroligin-3 and Mate Preferencecontrasting
confidence: 41%
“…While it has been documented that some of these brain regions (e.g. POA) can vary in neuronal properties with social structure, hormone levels, and copulation in males [White and Fernald, 1993;Prince et al, 1998;White et al, 2002;Sakuma, 2008], an analogous situation in females is unlikely in the current study. Female X. nigrensis breed year-round ; we did not detect any relationship between circulating estradiol levels and neuroligin-3 expression and females were not allowed to physically interact with males (online suppl.…”
Section: Neuroligin-3 and Mate Preferencecontrasting
confidence: 41%
“…Lesion studies have revealed that receptivity can be abolished without affecting approach to a sexually active male [13] while approach can be affected without reducing receptivity [14]. Some lesions may even enhance receptivity while reducing sexual approach [15]. Thus, the fact that the brain structures and the ER subtype involved in receptivity and proceptivity are quite well known does not mean that this applies to sexual approach behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…É possível, também, que áreas como a amígdala medial e área pre-óptica medial do hipotálamo, importantes regiões encefálicas envolvidas com o comportamento de motivação sexual (SAKUMA, 2008;WILL;HULL;DOMINGUEZ, 2014), possam ter sido afetadas pelo estresse pré-natal. Além disso, trabalhos mostram que a sensibilidade a odores, como os feromônios, os quais desempenham um eminente papel no comportamento sexual de ratos, agem tanto no sistema olfatório acessório quanto no sistema olfatório principal.…”
Section: Discussionunclassified